NETWORK SYSTEM IMPLEMENTATION USING MIKROTIK AND AT SMK NEGERI 9 MEDAN - Muhammad Donni Lesmana Siahaan; Iskandar Iskandar (Sean Institute, 2022)
SMK Negeri 9 Medan is a school located on Jl. Patriot No. 20 A, Lalang, Kec. Medan Sunggal. This school is a school that is in great demand because this school has several majors related to computers. Besides that, there are also many labs for doing computer practicum. But there are problems that occur in the computer lab network. The network often has problems when logging in to the internet and so on. For this reason, it is necessary to have adequate internet network management, a stable network connection. And internet bandwidth management is needed so that it can be shared on average among users or internet users and to improve security to make it easier to monitor its use. In this study, the focus is on hacking the network system using a proxy, namely IP configuration, network topology and network design. To build a more stable network, namely using Winbox.